Timber-concrete composite beams with special shear connectors. - Salam, S.A. (1982)
Four T-beams made up of concrete flanges and timber ribs were tested in the laboratory up to failure. Two rows of 10mm diameter bolts with large heads were used as shear connectors and three classes of timber (Chengal hardwood,light red and white meranti softwoods) were used for the tests. Though in some cases there was a slip at the interface between the timber and concrete and disturbance in strain distribution,the theoretical ultimate loads calculated on the basis of strength properties of the materials and strain compatibility show a complete agreement with the experimental loads. The difficult part of the work was the prediction of strength and other properties of timber due to a wide variation between the results obtained from BS 373 : 1957 tests and the values given in the Malaysian Code of Practice.